Application of Santri Religious Character Education in Islamic Boarding Schools (Case Study at An Nur Centre Islamic Boarding School, North Ende District, Ende Regency) - Ishak Umar; Muh Nur Rochim Maksum (CV. Rayyan Dwi Bharata, 2023)
Teachers are one of the components in education, including in Islamic religious education which greatly determines the success or failure of the objectives of Islamic religious education. In the teaching and learning process, the teacher not only acts as a conveyer of knowledge, but also is responsible for the development of the personality of students. The teacher must create the learning process in such a way, so that it can stimulate learners to learn effectively and dynamically in meeting and achieving the expected goals. Islamic education is currently faced with a very big challenge because it is not over with the rolling of the industrial era 4.0, We are surprised by the emergence of the era of society 5.0 which must be faced and become a challenge in the world of Islamic education. With the progress achieved in the field of science and technology, it will further trigger changes that occur in various fields of human life which at the same time have an impact on shifting cultural and religious values in human life. These are the challenges that must be anticipated as early as possible so that the existing challenges do not become a threat but become a promising opportunity. The formulation of the problem in this study is how the challenges of Islamic religious education teachers in facing the era of society 5.0. This research uses library research. In the data collection technique, researchers will explore data in accordance with the discussion of the challenges of Islamic religious education teachers in facing the era of society 5.0. Research results: Islamic religious education teachers must have 3 (three) abilities including the following: Ability to solve a problem, The ability to be able to think critically, and the ability to be creative in facing the challenges posed by the emergence of the era of society 5.0.